2021
DOI: 10.1080/10376178.2021.1927771
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of experiences of asylum-seeker women of living in detention centres: confinement versus safety

Abstract: A qualitative study of experiences of asylum-seeker women of living in detention centres: confinement versus safetyBackground: Australia has been at the forefront of legislation for compulsory detention for asylum seekers arriving by boat. Iranians are amongst the highest number of boat arrivals.More women than men have been subject to compulsory detention. Women, generally, face more health-threatening problems rather than men in detention, yet, remain understudied in health and social research. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Feelings of hopelessness, worry, despair, and fear (see Figure 2). The immigration detainees whose stories were captured in the studies (Cleveland et al, 2018;Coffey et al, 2010;Kronick et al, (2018); Passardi et al, 2022;Peterie, 2018;Shishehgar et al, 2021) reported that they were treated like criminals and kept in jail-like or prison-like facilities. Here, the culture of detention creates a loss of individual freedom and a violation of the detainees' human rights because they do not have the liberty to move around within the detention facilities or even go out of the facility.…”
Section: Metaphors/storylinesmentioning
confidence: 99%
See 4 more Smart Citations
“…Feelings of hopelessness, worry, despair, and fear (see Figure 2). The immigration detainees whose stories were captured in the studies (Cleveland et al, 2018;Coffey et al, 2010;Kronick et al, (2018); Passardi et al, 2022;Peterie, 2018;Shishehgar et al, 2021) reported that they were treated like criminals and kept in jail-like or prison-like facilities. Here, the culture of detention creates a loss of individual freedom and a violation of the detainees' human rights because they do not have the liberty to move around within the detention facilities or even go out of the facility.…”
Section: Metaphors/storylinesmentioning
confidence: 99%
“…Here, the culture of detention creates a loss of individual freedom and a violation of the detainees' human rights because they do not have the liberty to move around within the detention facilities or even go out of the facility. Detainees in the study (Shishehgar et al, 2021) reported that their rooms were like cages, closed and confined environments unsuitable for living in, and they wished they were freed.…”
Section: Metaphors/storylinesmentioning
confidence: 99%
See 3 more Smart Citations